THE STATUS OF THE STUDY GIDROMELNITSY ORIENTED ALCOHOL PRODUCTION - Ковальов, Сергій Федорович (Eastern-European Journal of Enterprise Technologies, 2012)
The analysis of maked work is carried out concerned the possibility of applying the hydrogrinding process in the alcohol industry. A variant of the implementation of hydrogrinding through the use hydromill as multifunctional machine is proposed.